Novel therapies for severe asthma in children and adults - Delimpoura, Vasiliki (Breathe (Sheff), 2018)
The heterogeneous nature of asthma requires personalised treatments. Monoclonal antibody treatments showed good efficacy, and should be considered when symptoms are poorly controlled despite good inhaler technique, compliance and controlled comorbidities. http://ow.ly/UWpg30hImQh